PENAMBAHAN DALAM EKRANISASI NOVEL ANTARES KARYA RWEINDA KE WEB SERIES - Ika Ananda Putri; Sri Muryati; Sukarno Sukarno (Universitas Batanghari, 2023)
This study aims to describe the form of ecranization of the additional aspects of the Antares novel to the Antares web series. This research use desciptive qualitative approach. The data in this study is the addition of plot, character, and setting in the Antares web series from the Antares novel. The data sources used are the novel Antares by Rweinda published by Loveable in 2020 and the web series Antares, produced by Manoj Punjabi and directed by Rizal Mantovani. Data collection techniques are through reading, viewing documentation, and taking notes. The data analysis technique used is comparative analysis. The results of this study obtained the form of adding plots, adding characters, and adding backgrounds which were shown through scenes in the Antares web series. There are thirty additional scenes that can be classified into thirteen scenes that show the addition of the plot (events), six scenes that show the addition of characters, and eleven scenes that show the addition of the setting. Additions are needed for the sake of a filmic angle and are still relevant to the overall content of the story.